THE INFLUENCE OF ORGANIZATIONAL ACTIVENESS AND LEARNING ACHIEVEMENT ON WORK READINESS IN MANAGEMENT - Samene, Fransiska; Kurniawati, Rohmah (Sekolah tinggi ilmu ekonomi pemuda, 2024)
The problem of this research is that the 2022 management study program students who will soon complete their education have good work readiness in the midst of increasingly fierce job competition with the qualification of soft skills and hard skills needs of each student in the 2022 management study program. This type of research is quantitative. The data collection technique in this study is multiple regression analysis. By using data collection techniques by means of questionnaires and documentation. before the questionnaire research was carried out, the validity and reliability tests were carried out using the help of the SPSS application. And with a research population of 41 students. After collecting the data, the classical assumption test was carried out. From the results of data analysis, it can be known that the coefficient of determination (R2) is 0.537 or 53.7%. Thus this value means that the organizational activeness (X1) and learning achievement (X2) contribute 53.7% to work readiness (Y) while the remaining 46.3% is influenced by other variables outside the study.From the results of the research that has been done, it shows that there is an influence on organizational activeness and student learning achievement on student work readiness, therefore it can be concluded that the more active students participate in organizations and are supported by high learning achievements, the better student work readiness will be in the world of work.